POTENSI PENGGUNAAN CAMPURAN SLAG NIKEL DAN FLY ASH SEBAGAI MATERIAL PERKERASAN JALAN - Rifanni Wiziarti; Wiwik Rahayu (Racic : Rab Construction Research, 2022)
The reuse of recycled materials on a large scale for geotechnical projects, such as in road pavements, will make it more economical and support environmental sustainability. Nickel slag and fly ash are examples of by-products of ferronickel and coal processing. In this study, a mixture of nickel slag and fly ash was investigated to be an alternative material for road pavement structures. The use of Class F fly ash is used as a filler and stabilization material. Laboratory testing is planned for the composition of the mixture of 5%, 8%, 11%, 14%, 17%, and 20% FA in the design criteria for compaction test (modified proctor), California Bearing Ratio (CBR), swelling potential and permeability . The results showed an increase in CBR values ​​for all mixtures. The composition of 11% FA has a minimum of 90% CBR value in soaked conditions. The potential for swelling still meets the maximum value limit of 0.5% (low degree of expansion). Permeability coefficients are only in the range of greater than 10-5 m/sec (medium permeability) where mixed combinations are categorized for roads with traffic volumes less than 500 vehicles/day.